2006
DOI: 10.1002/erv.771
|View full text |Cite
|
Sign up to set email alerts
|

Thought suppression in obese and non‐obese restrained eaters: piece of cake or forbidden fruit?

Abstract: The findings suggest that disinhibited restrainers, irrespective of their weight status, report a high tendency to suppress thoughts. Given Wegner's theoretical account, this may be associated with preoccupations and self-control difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
2
11
0
3
Order By: Relevance
“…It follows that obese and overweight individuals may have difficulties controlling their thoughts of food or thoughts concerning their shape and weight. This phenomenon may lead to overeating because thoughts of food increase the desire to eat [13]. Moreover, Engel et al [15] showed that attentional avoidance of body and shape concerns -a dysfunctional cognitive strategy -increases such concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that obese and overweight individuals may have difficulties controlling their thoughts of food or thoughts concerning their shape and weight. This phenomenon may lead to overeating because thoughts of food increase the desire to eat [13]. Moreover, Engel et al [15] showed that attentional avoidance of body and shape concerns -a dysfunctional cognitive strategy -increases such concerns.…”
Section: Discussionmentioning
confidence: 99%
“…There is a link between obesity and the selfdiscipline facet of the well-known NEO Personality Inventory (NEO-PI-R), which is related to lack of Perseverance [10]. Obese persons who overeat have a strong tendency to suppress thoughts [13], which may make the suppressed thoughts (e.g., thoughts of food) become hyperaccessible, which in turn causes distress and increased food consumption [14]. This may explain why obese people overeat, despite their intentions to control their food intake.…”
Section: Obesity and The Four Facets Of Impulsivitymentioning
confidence: 99%
“…Western-style diets, particularly those that are rich in trans-fatty acids, are powerful inducers of obesity and NAFLD, and therefore need to be avoided [106]. However, maintaining compliance with therapeutic measures involving restricted food consumption is emotionally challenging with a high rate of non-compliance [107]. Such patients require pharmacological therapies.…”
Section: Molecular Mechanisms Related To Treatments For Nafldmentioning
confidence: 99%
“…For instance, “restrained eaters” (i.e., individuals who show an above-average preoccupation with monitoring their food intake in order to avoid overeating and weight gain; see (44)) are more likely experience memory intrusions, including intrusive memories of food, if they are obese versus normal weight (45). There are also reports that restrained eaters are more likely to experience memory intrusions if they are susceptible to external eating (i.e., eating in response to food cues in the environment; (46), but see 47). These findings are consistent with the possibility that individuals who tend to lose control of their food intake may have deficits in memory control that make it difficult for them to resist thinking about food when confronted with food cues.…”
Section: Cognitive and Behavioral Inhibitory Processes And Energy Regmentioning
confidence: 99%